Cellular mechanisms of early tachycardia-induced ventricular dysfunction in the human heart. (25th November 2020) - Knierim, M; Pabel, S; Paulus, M; Rainer, P; Scherr, D; Hasenfuss, G; Maier, L; Streckfuss-Boemeke, K; Sossalla, S
Abstract: Background: Tachycardia-induced cardiomyopathy (TCM) is a reversible form of ventricular dysfunction caused by persistent tachycardia. Characterization of TCM is mainly based on artificially RV paced animal models. Moreover, the underlying mechanisms and time course from compensation to failure remain unclear. This study aimed to investigate early cellular remodeling of tachycardia-induced myocardial dysfunction in human myocardium. Methods and results: To elucidate early cellular electrophysiological targets mediating the transition to TCM, we chronically paced (120bpm vs 60bpm control) human induced pluripotent stem cell cardiomyocytes (hiPS-CM) for up to 7d. As a major substrate of cellular myocardial dysfunction, we investigated the influence of chronic tachycardia on cellular Ca cycling. After 24h of persistent tachycardia we detected a significant decrease in Ca transient (CaT) amplitude and reduced diastolic Ca levels (Fura-2). Meanwhile, Ca elimination time (RT80) was unchanged compared to control (n=44/42 cells / 8 diff.). Caffeine application was performed to evaluate sarcoplasmic reticulum (SR) Ca load. We found a shortening of caffeine-induced CaT relaxation time, whereas SR Ca load was unchanged (n=12/13 /8). Further illustrating the transition to TCM, CaT amplitude was progressively decreased after 7d of chronic tachycardia. In contrast to 24h of tachycardia, 7d persistent stimulation resulted in slowed relaxation (RT80, n=75/65 /7). These findings could be explained by a significant reduction of SERCA activity (Ksys-Kcaff) and SR Ca load (n=14/12 / 7). Diastolic Ca concentration remained reduced (n=75/65 /7), in total suggesting a shift to transsarcolemmal Ca elimination. Sodium measurements (SBFI) revealed a significant increase of intracellular sodium concentration (n=69/69 /5) after 7d of tachycardia. In patch clamp experiments we detected a prolongation of action potential duration as early as 24h after onset of tachycardia (n=26/21 /4), which persisted throughout 7d of pacing (n=8/12 /3). Resting membrane potential and action potential amplitude were not changed. Finally, we investigated tachycardia-mediated effects on pre-existing human heart failure (HF). 8h tachycardic stimulation (120bpm) of human HF ventricular trabeculae compromised systolic force, while diastolic tension and relaxation time were markedly increased compared to control (60bpm) (n=7/6 trabeculae /6 human hearts). The extensive molecular characterization of involved ion channels and pathways mediating transition to TCM is currently under investigation. Conclusion: This study demonstrates that a persistent tachycardia adversely alters cardiomyocyte excitation-contraction coupling via early electrophysiological cellular remodeling. In pre-existing HF persistent tachycardia strongly aggravates ventricular dysfunction. Our first translational investigation in human myocardium may help to understand the pathophysiology of an underrated and very prevalent disease. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Else-Kröner-Fresenius-Stiftung